Study of the facilitator and content as factors that can contribute to the effectiveness of the student development program in UiTM Pahang / Nor Atiqah Sahirah Sah'har Putra, Norsyahida Mohd Maamon and Raihana Samsul - Sah'har Putra, Nor Atiqah Sahirah; Mohd Maamon, Norsyahida; Samsul, Raihana (2010)
This study is to find out facilitator and content as factors that can contribute to the effectiveness of the Student Development Program (PPP) in UiTM Pahang. Questionnaires have been distributed by using systematic sampling technique method to 142 respondents and 92 questionnaires were collected back and others 50 questionnaires were rejected. Data analysis was done by using SPSS version 18. The study showed that most of the respondents agreed that facilitator and content play an important role to contribute to the effectiveness of Student Development Program (PPP). In this research report, we include the finding and from the finding there were some recommendation for improving facilitator skill and program content such as facilitator should expose respondents to the program and content must meet program objective in order to improve the effectiveness of Student Development Program (PPP). Besides that, there are two recommendations for future research such as sampling population and type of data collected. For the conclusion, this study perhaps can attract other researchers to explore much more detail towards this area of the study.